2009
DOI: 10.1111/j.1460-9568.2009.06642.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Nogo‐A antibody treatment promotes recovery of manual dexterity after unilateral cervical lesion in adult primates – re‐examination and extension of behavioral data

Abstract: In rodents and nonhuman primates subjected to spinal cord lesion, neutralizing the neurite growth inhibitor Nogo-A has been shown to promote regenerative axonal sprouting and functional recovery. The goal of the present report was to re-examine the data on the recovery of the primate manual dexterity using refined behavioral analyses and further statistical assessments, representing secondary outcome measures from the same manual dexterity test. Thirteen adult monkeys were studied; seven received an antiNogo-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 41 publications
(150 reference statements)
8
135
0
3
Order By: Relevance
“…For the present investigation, the motor performances at the modified Brinkman board task e static e and the rotating Brinkman board task e moving either clockwise or counterclockwise e were analysed. These two tasks were described in more detail in previous studies (Brinkman and Kuypers, 1973;Brinkman, 1984;Liu and Rouiller, 1999;Freund et al, 2009;Kaeser et al, 2010Kaeser et al, , 2011Schmidlin et al, 2011) and can be seen on the following web page: http://www.unifr.ch/neuro/rouiller/ research/brink.php. For each monkey, the performance of the left hand and the right hand were analysed separately.…”
Section: Subjects and Behavioural Tasksmentioning
confidence: 99%
“…For the present investigation, the motor performances at the modified Brinkman board task e static e and the rotating Brinkman board task e moving either clockwise or counterclockwise e were analysed. These two tasks were described in more detail in previous studies (Brinkman and Kuypers, 1973;Brinkman, 1984;Liu and Rouiller, 1999;Freund et al, 2009;Kaeser et al, 2010Kaeser et al, , 2011Schmidlin et al, 2011) and can be seen on the following web page: http://www.unifr.ch/neuro/rouiller/ research/brink.php. For each monkey, the performance of the left hand and the right hand were analysed separately.…”
Section: Subjects and Behavioural Tasksmentioning
confidence: 99%
“…For the CT, as an increase reflects a deficit, the functional recovery expressed in % is the ratio of the median pre-lesion CT (plateau) divided by the median post-lesion CT at plateau * 100. The effect of treatments post-lesion, demonstrated based on the test 1, are illustrated in detail in previous reports from this laboratory 14,15,17 . A further analysis may address the issue of the strategy, namely the temporal sequence of slots visited by the monkey (Figure 4B).…”
Section: Representative Resultsmentioning
confidence: 92%
“…As previously reported1 4,15 , these tasks represent the behavioral basis to investigate whether the spontaneous recovery from a lesion of the cervical cord may be enhanced with a specific treatment aimed at promoting axonal regeneration (Figure 8).…”
Section: Representative Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…10 The loss and recovery of forelimb motor function has been studied in several models of cervical SCI in rats, 4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] cats, [28][29][30] and primates. [31][32][33][34][35] All those studies demonstrated some extent of spontaneous motor function recovery, albeit with persisting deficits as a consequence of interruption of descending axonal tracts or segmental neuronal death. Despite these advances, there is still a need of cervical SCI models in which motor performance is comprehensively assessed in the long term to determine the motor components that show recovery and to link the chronic deficits with the neuroanatomical damage.…”
Section: Introductionmentioning
confidence: 97%